Genetic Relationship, Virulence Factors, Drug Resistance Profile and Biofilm Formation Ability of Vibrio parahaemolyticus Isolated From Mussel - Ashrafudoulla, Md.; Mizan, Md. Furkanur Rahaman; Park, Heedae; Byun, Kye-Hwan; Lee, Nari; Park, Si Hong; Ha, Sang-Do (Frontiers in Microbiology, 2019)
The objective of this study was to investigate the virulence factors, genetic relationship, antibiotic resistance profile and the biofilm formation ability of V. parahaemolyticus isolates on shrimp and mussel surfaces at 30°C. We used polymerase chain reaction (PCR) to examine the distribution of different genes, and Repetitive Extragenic Palindromic-PCR (REP-PCR) to compare the genetic relationship. Disk diffusion technique was used to assess antibiotic and multiple-antibiotic resistance. The biofilm formation assay, and field emission scanning electron microscopy (FE-SEM) were used to evaluate biofilm formation ability. Transmission Electron Microscope (TEM) was used to observe the morphological structure of bacterial cell. Our results indicated that the biofilm-associated genes, 16S rRNA, toxR, and tdh, were present in all the tested V. parahaemolyticus isolates. Most of the isolates exhibited a strong multiple-antibiotic resistance index with an average value of 0.57. All isolates shown strong genetic relationship and significant biofilm formation ability on shrimp and mussel surfaces. The continuous monitoring of V. parahaemolyticus antibiotic, molecular and biofilm characteristics is needed to increase seafood safety.